Information, representations and discourses about the iconic architecture of Brasilia: the case of Brasília magazine - Videsott, Luisa (Risco - Journal of Architecture and Urbanism, 2010)
The first series of the magazine Brasília, the official dissemination of Novacap, was published from January 1957 to May 1963. His iconographic, that is his photographs and the complex visual language articulated by its graphics, is the subject of the following article. It aims to draw attention to the speeches monthly distributed by the Novacap among the national's erudite readers and abroad. It is also proposes, conceptualising its editorial policy, to consider the possibility of the use of its information in historical research.